FIXED ASSETS AND MUSEUM FUNDS: FEATURES OF ACCOUNTING AND CONTROL IN THE PUBLIC SECTOR - Khorunzhak N.М.; Sysiuk , S.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The reform of public sector accounting is accompanied by the need to address problems related to the identification, valuation and recording of fixed assets and museum holdings. The presence of deficiencies in the accounting and control of such assets affects the rationality of spending budget funds and reduces the efficiency of the functioning of budgetary institutions. The article proposes a theoretical substantiation of the possibilities for the development and improvement of the reflection of museum funds, taking into account the experience of accounting for fixed assets of the public sector, substantiates an approach to the procedure for assessing and recognizing such values (objects), the documenting system and the scheme of their entry into institutions. To achieve comprehensiveness in matters of increasing the efficiency of the use of museum funds in the process of activity, the issues of organizing and monitoring the named values are considered, highlighting the tasks and methods of their implementation. The proposals are based on the analysis of management requests and challenges. The study is based on the rules, principles and procedures of accounting and control, which form the basis of their organization, methodology and practice. Their use allows you to systematize and generalize recommendations on the structure and procedure of the accounting and control process of fixed assets and museum funds of the public sector. These methods include: a critical analysis of legislative provisions, an assessment of the existing accounting and control systems by monitoring the level of provision of management requests, generalization of positive experience and modeling of their improved structures. The result of the research is proposals concerning the system for evaluating museum funds, the structure of accounting and control systems, which in their conceptual basis are guided by the optimization of accounting and control processes and their documentary support. In general, this will lead to an increase in the efficiency of the use of fixed assets and museum funds in the public sector. In the future, it is advisable to analyze the study of the above issues in the context of strengthening the relationship between accounting and stock accounting, as well as the formation of their unified computer information system. The problem of control should be investigated with a focus on computerization, improving the organization of interaction between various regulatory bodies and the development of forms of control.